Subaqueous soils of the Brazilian seagrass meadows: biogeochemistry, genesis, and classification - Nobrega, Gabriel Nuto (2017)
Seagrass meadows, or submerged aquatic vegetation, constitute an ecosystem with great importance to the coastal zone, and may be characterized as the most productive ecosystem on Earth. In addition to the provision of habitat for a wide variety of species, protection of the coastal zone and production of organic matter base for the marine trophic web, these environments have been recognized for their great capacity to store organic carbon in their soils and are, therefore, a priority area for the mitigation of increased carbon in the atmosphere. In spite of the great importance of these areas, there is little information about the soils of these ecosystems, mainly using an approach based on the genesis of its soils. Thus, this thesis covers 4 chapters aiming to: (i) evaluate changes in the characteristics of seagrass meadows publications in the last 50 years, identify knowledge gaps and priorities for future studies; (ii) to discuss the paradoxical lack of information on Brazilian seagrass meadows soils, stimulate studies to understand their characteristics and contribute to the correct inclusion of seagrass meadows soils in the Brazilian System for Soil Classification; (iii) characterize and investigate soils of seagrass meadows along the Brazilian coast, in order to understand the pedogenetic processes within these soils; and (iv) identify variations in the biogeochemical processes related to the dynamics of Fe, Mn and S along the Brazilian coast, aiming to provide an improved basis for the understanding of this ecosystem and subsidies for the use and protection policies of these coastal areas.